Impact of Collective Efficacy, Cohesion and Trust on Project Team Performance - Garima Mathur; Richa Banerjee; Silky Vigg Kushwah (AIBPM Publisher, 2019)
Team is an inevitable part of almost all organizations in the world but managing a project needs great deal of efforts and understanding among group members. There are many significant contributors to the success of team performance. To name a few are collective efficacy, cohesion and trust. Collective efficacy is the belief a group has pertaining to its capabilities. A team with high level of trust among members often results in to high level of performance (Ferda Erdem Janset OzenNuray Atsan, 2003). Similarly the people with strong Cohesion between them results in to effective team performance (Tessla Arakal, Dr. Sebastian Rupert Mampilly, 2017). The study emphasizes on student’s teams working on different projects. In a present study we have made an attempt to identify relationship between collective efficacy, cohesion and trust.